Design and Build Smart Agriculture Using Cognitive Internet of Things (C IoT) - Aries Dwi Indriyanti (Publikasi Indonesia, 2022)
In Indonesia, agriculture is required to be able to develop growth in the region and be able to produce agricultural products that have high competitiveness while also empowering the community. IoT, or commonly known as the Internet of Things (Internet of Things), allows us to connect to various things. For example, we can use a smart farm. This research leads to the implementation of a plant sprayer that uses the Cognitive internet of things that can be integrated into farmers and factories whose raw material uses corn. This irrigation system uses a NodeMCU microcontroller, automatic discharge using a DC water pump, a soil moisture sensor using a capacitive soil moisture v.2 sensor. The system used uses fuzzy logic algorithms as data processing. The sensor data shows the 70% soil moisture value displayed on the smartphone so that the system will water or not automatically until the soil moisture value is as needed. Soil moisture in this system is in 3 criteria, namely dry, normal, and wet. Watering produced by this system with an average time duration of 8 seconds. This farming system is designed to increase productivity and predict problems in agriculture. This analysis illustrates that the Cognitive internet of things has great potential in agricultural technology because it can increase and facilitate corn production for farmers.